Extraction spectrophotometric determination of pharmaceutical compounds. - Saad, B.B. (Universiti Sains Malaysia, 1994)
Simple, sensitive and fairly rapid method for the determination of noscapine (an opium alkaloid of pharmaceutical importance) is described. It is based on the measurement of the absorbance of the organic soluble ion association complex formed between the noscapine monocation and a bulky counter anion.